Trading firms and trading costs in services: The case of Sweden - Magnus Lodefalk; Hildegunn Kyvik Nordås (Örebro University School of Business, 2017)
This paper first portraits Swedish services exporters and services MNEs; second it analyses the determinants of services exports and affiliate sales; and third it studies the choice of mode of entering a foreign market. Emanating from a heterogeneous firm internationalization model, the main contribution of the paper is to explore the interaction between firm characteristics and foreign market characteristics, particularly policy-induced services trade barriers, in shaping services trade and investment patterns. Exploiting a large and very detailed firm-level dataset for the 2008-2013 period, the descriptive analysis finds that most exporting firms export one or two products to a few, most often other Nordic countries. Still, firms that export to 25 or more markets account for more than 80% of total export value. Furthermore, firms that export to 20 countries export more than 60% to their main destination country. Similar patterns are found for affiliate sales. Using a gravity approach we then study the determinants of the extensive and intensive margin of exports and affiliate sales in pooled as well as sector level regressions. We find that trade costs, both natural and policy-induced have the largest impact on the extensive margin of trade, suggesting that trade costs facing services exporters are mainly in the form of fixed entry costs. This is further supported by the finding that incumbency is the most important determinant of future exports and affiliate sales, and incumbents tend to be protected and thrive behind trade barriers.
Keywords: D22; F13; 330; services trade; affiliate sales; trade costs; micro data; Sweden